In‐Plane Deformation Mechanics for Highly Stretchable Electronics. Issue 8 (22nd December 2016) - Su, Yewang; Ping, Xuecheng; Yu, Ki Jun; Lee, Jung Woo; Fan, Jonathan A.; Wang, Bo; Li, Ming; Li, Rui; Harburg, Daniel V.; Huang, YongAn; Yu, Cunjiang; Mao, Shimin; et al.
Abstract : Scissoring in thick bars suppresses buckling behavior in serpentine traces that have thicknesses greater than their widths, as detailed in a systematic set of analytical and experimental studies. Scissoring in thick copper traces enables elastic stretchability as large as ≈350%, corresponding to a sixfold improvement over previously reported values for thin geometries (≈60%).